Microfinance Handbook: An Institutional and Financial Perspective - Ledgerwood, Joanna (Washington, DC: World Bank, 2013)
The purpose of this handbook is to bring together in a single source guiding principles and tools that will promote sustainable microfinance and create viable institutions. It provides a comprehensive source for the design, implementation, evaluation, and management of microfinance activities. The book has three parts: part one takes a macroeconomic perspective toward general microfinance issues and is primarily non-technical. Part two narrows its focus to the provision of financial intermediation, taking a more technical approach and moving progressively toward more specific (or micro) issues. Part three, the most technical part of the handbook, focuses primarily on assessing the financial viability of microfinance institutions.